Healing below the ankle is possible in patients with diabetes mellitus and a forefoot gangrene. (June 2021) - Elgzyri, Targ; Apelqvist, Jan; Lindholm, Eero; Örneholm, Hedvig; Annersten Gershater, Magdalena
Background: Forefoot gangrene in patients with diabetes is a severe form of foot ulcers with risk of progress and major amputation. No large cohort studies have examined clinical characteristics and outcome of forefoot gangrene in patients with diabetes. The aim was to examine clinical characteristics and outcome of forefoot gangrene in patients with diabetes admitted to a diabetic foot centre. Methods: Patients with diabetes and foot ulcer consecutively presenting were included if they had forefoot gangrene (Wagner grade 4) at initial visit or developed forefoot gangrene during follow-up at diabetic foot centre. Patients were prospectively followed up until final outcome, either healing or death. The median follow-up period until healing was 41 (3–234) weeks. Results: Four hundred and seventy-six patients were included. The median age was 73 (35–95) years and 63% were males. Of the patients, 82% had cardiovascular disease and 16% had diabetic nephropathy. Vascular intervention was performed in 64%. Fifty-one patients (17% of surviving patients) healed after auto-amputation, 150 after minor amputation (48% of surviving patients), 103 had major amputation (33% of surviving patients) and 162 patients deceased unhealed. Ten patients were lost at follow-up. The median time to healing for all surviving patients was 41 (3–234) weeks; for auto-amputated, 48 (10–228) weeks; for minor amputated, 48 (6–234) weeks; and for major amputation, 32 (3–116) weeks. Conclusion: Healing without major amputation is possible in a large proportion of patients with diabetes and forefoot gangrene, despite these patients being elderly and with extensive co-morbidity.